Menciptakan Habitus Moderasi Beragama: Upaya Pondok Pesantren Sunan Pandanaran dalam Meneguhkan Islam Rahmatan Lil ‘Alamin - Muharis, Muharis (Medan Resource Center, 2023)
This research is important to do considering that currently Indonesia and even the world need a moderation model of religion as a solution for the emergence of various fundamentalist ideas that lead to acts of radicalism and terrorism in a plural-multi-religious-multicultural society. The main problem which is the object of study in this study is the form of internalization of religious moderation carried out by the Sunan Pandanaran Islamic Boarding School which is unique and unique. This study uses a sociological approach with the theory used is Pierre Bourdieu's